Adaptive Water Management Strategies for Subsistence Rice Farming Under Projected Rainfall Variability in Drought-Risk Khon Kaen, Thailand - Saraphirom, Phayom; Choenkwan, Sukanlaya; Promkhambut, Arunee; Jinai, Tansuda (Forest and Society, 2025)
This study offers new insights into adaptive water management for drought-prone subsistence rice farming in Ban Thum Sub-district, Khon Kaen Province, Thailand. By triangulating climate science, agronomy, and farmers’ socio-economic conditions, we assess drought risk and identify feasible adaptation strategies. The analysis integrates 30 years of observed climate data (1994–2023), mid-century projections (2024–2053) under SSP 245 and SSP 585, as well as semi-structured interviews with farmers. Stage-specific effective rainfall, crop evapotranspiration, and supplemental water requirements were calculated. Although total rainfall is projected to rise slightly, severe and moderate droughts are expected to remain frequent, particularly during the heading and ripening stages. In drought years, sustaining yields of 200–300 kg rai⁻¹ will require an additional 200–1,300 m³ rai⁻¹ of water. Groundwater wells and large farm ponds are technically effective but financially inaccessible to most smallholders; smaller ponds represent a more affordable alternative. The findings underscore the importance of targeted adaptation, including enhanced on-farm storage, optimized irrigation scheduling, and supportive policies such as low-interest loans and infrastructure subsidies. By linking climate projections to local capacities, this study provides a practical roadmap for strengthening rice-farming resilience and safeguarding food security in one of Thailand’s most climate-vulnerable regions.